2010
DOI: 10.1111/j.1743-6109.2009.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

The International Index of Erectile Function: Development of an Adapted Tool for Use in HIV-Positive Men Who Have Sex with Men

Abstract: Introduction Erectile dysfunction is common in HIV-positive men who have sex with men (MSM). A standardized scale is needed to assess erectile function in clinical practice and research studies. Aim The International Index of Erectile Function (IIEF) is a widely accepted tool for assessing erectile function designed for heterosexual men. We modified the tool for MSM. We present an analysis of internal consistency of the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 8 publications
3
79
0
Order By: Relevance
“…In this scale, higher scores characterize better functioning or satisfaction during sex. Erectile functioning was determined by the summed scores of a modified version of the IIEF-MSM (Coyne et al, 2010). The IIEF-MSM avoids assumptions in the original IIEF that all men engage in penetrative sexual intercourse during sexual activity.…”
Section: Methodsmentioning
confidence: 99%
“…In this scale, higher scores characterize better functioning or satisfaction during sex. Erectile functioning was determined by the summed scores of a modified version of the IIEF-MSM (Coyne et al, 2010). The IIEF-MSM avoids assumptions in the original IIEF that all men engage in penetrative sexual intercourse during sexual activity.…”
Section: Methodsmentioning
confidence: 99%
“…However, differences were found between groups on marital status, v 2 (3) = 13.805, p = .003, with heterosexual men reporting higher rates of married/living together. Additionally, gay men with sexual problems scored significantly lower on the International Index of Erectile FunctionVersion for Men Who Have Sex with Men (IIEF-MSM; Coyne et al 2010), compared with gay men without sexual problems, t(45) = 4.467, p \ .001. Likewise, heterosexual men with sexual problems scored significantly lower on the International Index of Erectile Function (IIEF; Rosen et al 1997), compared with heterosexual men without sexual problems, t(60) = 3.369, p = .001.…”
Section: Characterization Of the Samplementioning
confidence: 96%
“…The Portuguese version also presented good psychometric properties, with test-retest analysis indicated correlations between two administrations with a 2 weeks interval ranging from .69 and .90, and Cronbach's alpha values between .72 and .86 (Quinta-Gomes and Nobre 2012b). A modified version of the IIEF, for men who have sex with men was used with gay men (IIEF-MSM; Coyne et al 2010). The psychometric study suggested good reliability with Cronbach's alpha values of ranging from .82, .83, and .89 for erectile, orgasmic function and sexual desire function domains (Coyne et al 2010).…”
Section: The International Index Of Erectile Function (Iief)mentioning
confidence: 99%
See 2 more Smart Citations